Optimization of Formation Reaction Conversions of Fatty Acid Amidopropyl Dimethylamines - Acikalin, Korkut (CARL HANSER VERLAG, 2019)
The present study focuses on the optimization of conversions of cocamidopropyl and palmamidopropyl dimethylamine formation reactions in which the byproduct water was or was not distilled during the syntheses. Reactions without water removal were conducted in conjunction with a central composite experimental design to investigate the effects of reaction temperature (120 degrees C-160 degrees C) and reaction time (4 h -10 h) on the reaction conversions. Quadratic models were observed to be the best-fitting models, with 99.9% confidence levels, and yielded errors less than 2.86 %, including the control experiments. Response surface graphs demonstrated that the optimum reaction temperature and reaction time were 155 degrees C-160 degrees C and 6.85 h - 7.45 h, respectively, with 83%-84% reaction conversions. In contrast, the reactions that included water removal were performed at a fixed temperature of 160 degrees C and a varying reaction time between 3 h and 7 h. The results were fitted to secondorder polynomial equations. The optimum reaction conversions were observed to be similar to 95% for reaction times of 6.62-7.05 h. The increase in reaction conversions compared with the conversions obtained in the absence of water removal revealed that a cost saving of 11.9 % can be achieved with respect to raw material cost per 1 ton of amidoamine produced.
Keywords: Cocamidopropyl dimethylamine; palmamidopropyl dimethylamine; reaction conversion; optimization; response surface methodology; BETAINE; Chemistry; Engineering